Championing reproductive and perinatal health with the recovery community: improving access to healthcare and health promotion resources to support recovery - Feld, Hartley; Elswick, Alex; Byard, Jeremy; Beckett, Whitney; Fallin-Bennett, Amanda (Frontiers in Public Health, 2025)
Peer recovery support services are instrumental in the promotion of long-term recovery primarily by focusing on building the recovery capital of people with substance use disorders. Women may have specific health-related needs that are not generally part of recovery support staff training. Our team co-created a model by training people with lived experience as coaches to promote the health of women with SUD during the critical period of their reproductive years when mortality from overdose risk is high and can be compounded by issues surrounding pregnancy. We explored the outcomes of a small pilot test of this model to promote reproductive autonomy in a recovery community center (RCC). The RCC and the champion-trained peer recovery coach were able to increase their reach to women of reproductive age and facilitated linkage to healthcare and health-promoting resources. The model has the potential to improve the participants' abilities to access reproductive and perinatal health resources and healthcare that could lead to improvements in their recovery.